2013
DOI: 10.2478/pralin-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

CASMACAT: An Open Source Workbench for Advanced Computer Aided Translation

Abstract: We describe an open source workbench that offers advanced computer aided translation (CAT) functionality: post-editing machine translation (MT), interactive translation prediction (ITP), visualization of word alignment, extensive logging with replay mode, integration with eye trackers and e-pen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…The feedback signal can range from a simple word correction to complex, indeterministic ones, such as an eye-gaze tracking, combined with a handwritten correction, as in Alabau et al (2013). The features of the signal and its meaning determine the nature and behavior of the IMT system.…”
Section: Interactive Neural Machine Translationmentioning
confidence: 99%
“…The feedback signal can range from a simple word correction to complex, indeterministic ones, such as an eye-gaze tracking, combined with a handwritten correction, as in Alabau et al (2013). The features of the signal and its meaning determine the nature and behavior of the IMT system.…”
Section: Interactive Neural Machine Translationmentioning
confidence: 99%
“…The main logging tool was the CASMACAT translators' workbench (Alabau, Bonk, et al 2013). This tool can be used as a translation environment with the additional advantage that it contains keystroke logging and mouse-tracking software suited for subsequent translation process research.…”
Section: Methodsmentioning
confidence: 99%
“…The results of user trials (Macklovitch, 2006) showed gains in productivity (measured in number of words translated per hour) of around 15-20%. A number of projects (Koehn, 2009;Ortiz-Martínez, 2011;Alabau et al, 2010Alabau et al, , 2013 have recently continued the research where TransType2 left it off. As regards tools, both Caitra (Koehn, 2009) and the CASMACAT Workbench (Alabau et al, 2013) are web applications with an underlying SMT-based ITP system.…”
Section: Related Workmentioning
confidence: 99%
“…A number of projects (Koehn, 2009;Ortiz-Martínez, 2011;Alabau et al, 2010Alabau et al, , 2013 have recently continued the research where TransType2 left it off. As regards tools, both Caitra (Koehn, 2009) and the CASMACAT Workbench (Alabau et al, 2013) are web applications with an underlying SMT-based ITP system. Caitra consults the internal translation table of the SMT system Moses (Koehn et al, 2007) in order to show the most likely translation options to the human translator.…”
Section: Related Workmentioning
confidence: 99%